Factors affecting the export demand of Malaysian palm oil - Nur Aliyah Jazuli; Assis Kamu (e-VIBS, Faculty of Science and Natural Resources, 2019)
This paper develops studies made on determinants for export demand of the Malaysian palm oil in the world market especially in top importing countries. The factors comprised in the analysis such as total area planted, production of palm oil, number of population, country’s import of palm oil, price of palm oil and its substitutes, GDP of own country and importing countries, exchange rates (MYR/USD) and even to downstream details on number of mills, refineries and biodiesel with oleochemical plants and number of production of palm oil’s food and non-food products. For this paper, Ordinary Least Squares (OLS) Regression using model building approach of Multiple Linear Regression (MLR) is being used to obtain the best model equation. Result obtained reflects a different findings from other studies regarding the factors that affect the export demand which are the production of palm oil, price of substitutes (fish oil), and palm oil based product (RBD palm olein) that significantly affects the demand for Malaysian palm oil export.